From research to practice: Incorporating consumer bankruptcy into community development initiatives. (2nd January 2023) - Hackney, Donald; Friesner, Dan; Patil, Vivek
ABSTRACT: This manuscript presents a case study illustrating how simple, visual analytics tools can be used to longitudinally assess consumer bankruptcy filings in a single community. In doing so, it provides a template for leaders in other communities to follow in conducting their own assessments. The case study focuses on the Logan neighborhood in Spokane, WA, a blue collar neighborhood which is home to Gonzaga University. This allows for simple comparisons to assess evolutionary changes in bankruptcy filings, within the Logan neighborhood over time, as well as comparisons to other Spokane neighborhoods that have less diversity and higher mean incomes.